Fabrication and characterization of porous bioceramic made from bovine bone powder mixed calcium phosphate glass - Sittiporn Punyanitya (2019)
© 2019 Trans Tech Publications Ltd, Switzerland. Bovine bone xenograft was selected bioactive material currently widespread acceptable for using as human bone void filler. In this paper we described a new porous bioceramic block fabricated from bovine bone powders mixed with calcium phosphate glass. The characterized methods were atomic absorption spectrometer, x-ray diffraction, scanning electron microscope, energy dispersion x-ray spectroscopy, diffusion test, bending test, compressive test and Archimedes' principle. The final products showed interconnecting pores size range 100 to 500 μm, apparent porosity about 52% and mole ratio of Ca:P as 1.65. The toxic elements such as arsenic, cadmium, mercury, and lead were lower standard limits of ASTM I (American Society for Testing and Materials International). The samples had a compressive strength more than 400 kg/cm2. So, this object can be useful as an alternative choice for human bone substitute in the vertical compression load bearing area.